Influence of negative affect on decision making in women with restrictive and binge-purge type anorexia nervosa. (30th May 2016) - Danner, Unna N.; Sternheim, Lot; Bijsterbosch, Jojanneke M.; Dingemans, Alexandra E.; Evers, Catharine; van Elburg, Annemarie A.
Abstract: The present study aims to examine the influence of negative affect on decision making in women with anorexia nervosa (AN) compared to healthy control women and, secondly, to assess differences between the restrictive (ANR) and binge-purge (ANBP) subtypes. One hundred four women (32 with ANR, 32 with ANBP, and 40 healthy controls) participated. All women were asked to watch either a negative or a control film fragment, both followed by the Bechara Gambling Task (BGT). Before and after the fragments negative affect was measured. Additionally, relevant characteristics (e.g., overall depressive symptoms) were assessed. Differences in negative affect did not influence decision making performance. Independent of affective state, decision making was found to be impaired in women with ANBP (no learning effect on the BGT), but not in women with ANR. These findings highlight the importance of considering different AN subtypes when examining decision making processes. However, the role of negative affect on decision making remains uncertain. Since other affect related factors such as affect dysregulation may also play a role, future studies on decision making in AN should take the role of affect into account. Highlights: We examine the influence of affect on decision making in anorexia nervosa. We test decision making differences between anorexia nervosa subtypes. Anorexia nervosa subtypes respond differently to negative affect induction. Binge-purge subtype shows impaired decision making, but restrictive type not.